2013
DOI: 10.3928/1081597x-20121228-04
|View full text |Cite
|
Sign up to set email alerts
|

Intracorneal Ring Segments Implantation Followed by Same-day Topography-guided PRK and Corneal Collagen CXL in Low to Moderate Keratoconus

Abstract: The combination of ICRS implantation followed by sequential same-day topography-guided PRK/CXL may be a reasonable option for improving visual acuity in patients with low to moderate keratoconus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 15 publications
2
45
1
Order By: Relevance
“…The Ocular Wavefront Analyser and the Corneal Wavefront Analyser are reliable and have been recommended for use in refractive surgery, even though the Hartmann-Shack device was favored. 28 Although studies [12][13][14][15][16][18][19][20][21]23,34,35 have shown similar significant improvements in most of the tested visual functions, they have been conducted on a different population sample and/or have not agreed on all findings, partly because of the variation in the surgical protocol, and data collection/analysis method or follow-up duration. Additionally, many of these studies have been performed on a few eyes 15,16,20,21,23 and have used a format which is different from that recommended 25,26 in presenting their graphic data, thus making it difficult to directly compare results between studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Ocular Wavefront Analyser and the Corneal Wavefront Analyser are reliable and have been recommended for use in refractive surgery, even though the Hartmann-Shack device was favored. 28 Although studies [12][13][14][15][16][18][19][20][21]23,34,35 have shown similar significant improvements in most of the tested visual functions, they have been conducted on a different population sample and/or have not agreed on all findings, partly because of the variation in the surgical protocol, and data collection/analysis method or follow-up duration. Additionally, many of these studies have been performed on a few eyes 15,16,20,21,23 and have used a format which is different from that recommended 25,26 in presenting their graphic data, thus making it difficult to directly compare results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 However, a combination of various techniques such as conductive keratoplasty, 10 photorefractive keratectomy (PRK), [11][12][13][14] intrastromal corneal ring (ISCR) implantation plus PRK, 15,16 non-topography-guided PRK after ISCR implantation, 17 and simultaneous wavefront-guided PRK 18 with CXL maximizes the results by providing an overall additive effect on visual acuity, keratometry, and stability of the condition. 11,15,16,[19][20][21][22][23] Same-day simultaneous topography-guided PRK and CXL was shown to be superior to sequential CXL with later PRK in the visual rehabilitation of progressing keratoconus. 24 Despite the reported safety and improvements in visual functions associated with a same-day combined surgical approach, few studies have followed up the patients beyond 6 months postoperatively and the procedure is uncommon among practitioners in the Middle East despite the increasing number of keratoconus referrals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Mahipal Sachdev: We have been performing ICRS for more than 5 years now and results in most patients are good. There is signifi cant improvement in UCVA and BCVA in about 70% patients which is maintained long term ( Figure 1).…”
Section: Summary (Charu Khurana): Intra-corneal Ring Segments (Icrs)mentioning
confidence: 99%
“…The results in my hands have been favourable, with stable topography 1 year post treatment and signifi cant improvement of biomechanics. 14,15 Charu Khurana: How oft en do you perform Intra-corneal ring segments (ICRS) for keratoconus patients? Sudhank Bharti: ICRS can provide an improvement in visual acuity because they improve the central corneal curvature.…”
Section: Rohit Shett Ymentioning
confidence: 99%